Dinâmica e manejo do complexo afídeos - nanismo-amarelo em trigo - Bilibio, Marcos Ivan (2019)
Aphids are the main pests of winter cereals. In addition to direct damage by sap suction, they are vectors of Barley yellow dwarf virus and Cereal yellow dwarf virus (B / CYDV). It is necessary to enable the sustainable management of this pathosystem by improving population monitoring methods and decision-making criteria (action levels), estimate the damage to production caused by B / CYDV epidemics and determine the effectiveness and profitability of insecticide management to control the problem over time. The aim of this study was to broaden the understanding of the aphid population dynamics and to evaluate insecticide management alternatives to support the management of the aphid-virose complex of yellow dwarfism in wheat crop, in Passo Fundo/RS region. In the 2013/14/15 and 16 wheat crop seasons, the aphid population was monitored using a yellow - tray trap with water and direct counting on plants in the control plots, in which five systems were evaluated: Insecticide management: TT - total treatment to evaluate the productive potential (insecticide seed treatment + weekly insecticide spraying on the shoot); TS - seed treatment only; PA - only insecticides in shoots when reaching action level (NA); TS + PA and SI - no insecticides (witness). In 2013, the trial was not treated with TS + PA. Generally, when below NA, the number of aphids in plants and trays fluctuated proportionally. After reaching NA, the aphid population increased significantly in both evaluations (plants and trays). In the average of the 2013/14/15 and 16 harvests, in the TT, a yield of 4,573.95 kg/ha was obtained. Considering this treatment as a reference, the second treatment with higher yield was TS + PA (4,121.26 kg / ha), followed by PA (3,946.69 kg/ha) and TS (3,921.62 kg/ha). At the other extreme, SI provided 3,626.05 kg ha. The TS + PA treatment presented the best cost x benefit ratio, with a net revenue of R$ 287.49 h -1, compared to the control (SI).